A new tool for assessing workforce management policies over time : extending the dynamic retention model - Asch, Beth J.; Mattock, Michael G., 1961-; Hosek, James R.; Rand eBooks (Santa Monica, CA : RAND, 2013)
The dynamic retention model (DRM) is a state-of-the-art modeling capability that supports decisionmaking about workforce management policy. The DRM can be applied in a wide variety of workforce contexts for a variety of compensation and personnel policies, though to date the focus has been on supporting military compensation decisions to sustain the all-volunteer force in the United States. While the DRM is an extremely powerful tool, a drawback in the use of the model to date is that it has focused on the steady state. That is, implementations of the model to date show only the retention and cost effects of alternative policies when the entire workforce is under the new policy versus when the workforce is under existing policy. The research presented in this report extends DRM to allow simulations of the effects of alternative policies both in the steady state and in the transition to the steady state. It also shows the effects of alternative implementation strategies and how different policies can affect how quickly the population and costs move toward the new steady state.
Introduction -- Extending the DRM to Incorporate the Transition Period -- Application to Military Retirement Reform -- Concluding Thoughts -- Appendix: Additional Model Results Related to Retention Effects.
"RAND National Defense Research Institute."
"This research was conducted within the Forces and Resources Policy Center of the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 71-73).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States -- Armed Forces -- Personnel management -- Evaluation; United States -- Armed Forces -- Personnel management -- Mathematical models; Electronic books